The Relationship between TNF- Levels and Platelet Counts in Dengue Hemorrhagic Fever Patients in RSUD DR. Soedjono Selong, East Lombok Regency, West Nusa Tenggara Province - Herlinawati, Herlinawati; Hermawati, Resna; Azmi, Fahriana; Sabariah, Sabariah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Dengue hemorrhagic fever is an infectious disease caused by the dengue virus (DENV) and transmitted through the Aedes aegypti mosquito. Macrophage infection by the dengue virus causes activation of T-helper and T-cytotoxic so that lymphokines and interferon-gamma are produced. Interferon-gamma will activate monocytes so that various inflammatory mediators are secreted such as TNF-, IL-1, and IL-6 which results in endothelial cell dysfunction and plasma leakage. Vascular disorders that occur are characterized by a decrease in the number of platelets. This study aims to determine the relationship between TNF- levels and the number of platelets in patients with dengue hemorrhagic fever at RSUD DR. Soedjono Selong, East Lombok Regency, NTB Province. Analytical observation with cross-sectional design. This research was conducted in RSUD DR. Soedjono Selong; the time of the study was April-September 2021. The sample of this study was dengue hemorrhagic fever patients who were hospitalized at RSUD DR. Soedjono Selong as many as 70 people. This research uses the method of consecutive sampling, with the independent variable in the form of TNF- and the dependent variable in the form of platelets. The platelet count was checked withThe Sysmex XN 550 autoanalyzer uses the hydrodynamic impedance counting method (sheath flow DC method) and checks the levels of TNF-? with an ELISA kit. Data analysis was carried out using SPSS, namely univariate test, and bivariate test with Chi-square. There were 27 (38.6%) males and 43 (61.4%) females with a total of 70 patients. The age of the youngest patient was 1 year and the age of the oldest patient was 66 years with a mean age of 24 years ± 20 years. All 70 dengue hemorrhagic fever patients had normal TNF- levels. There were 30 (48.6%) with normal platelet counts and 36 (51.4%) with abnormal platelet counts. And found a non-significant relationship between levels of TNF- with the number of platelets with a value (p = 0.908). There is no relationship between levels of TNF- with platelet count in dengue hemorrhagic fever patients in RSUD DR. Soedjono Selong, East Lombok Regency, NTB Province.